An Extracytoplasmic-Function Sigma Factor Is Involved in a Pathway Controlling β-Exotoxin I Production in Bacillus thuringiensis subsp. thuringiensis Strain 407-1 - Espinasse, Sylvain (American Society for Microbiology, 2004)
β-Exotoxin I is an insecticidal nucleotide analogue secreted by various Bacillus thuringiensis strains. In this report, we describe the characterization and transcriptional analysis of a gene cluster, designated sigW-ecfX-ecfY, that is essential for β-exotoxin I production in B. thuringiensis subsp. thuringiensis strain 407-1. In this strain, the disruption of the sigW cluster resulted in nontoxic culture supernatants. sigW encodes a protein of 177 residues that is 97 and 94% identical to two putative RNA polymerase extracytoplasmic-function-type sigma factors from Bacillus anthracis strain Ames and Bacillus cereus strain ATCC 14579, respectively. It is also 50, 30, and 26% identical to SigW from Clostridium perfringens and SigW and SigX from Bacillus subtilis, respectively. EcfX, encoded by the gene following sigW, significantly repressed the expression of sigW when both genes were overtranscribed, suggesting that it could be the anti-sigma factor of SigW. Following the loss of its curable cry plasmid, strain 407 became unable to synthesize crystal toxins, in contrast to the mutant strain 407-1(Cry(−))(Pig(+)), which overproduced this molecule in the absence of this plasmid. Transcriptional analysis of sigW indicated that this gene was expressed during the stationary phase and only in the 407-1(Cry(−))(Pig(+)) mutant. This suggests that in the wild type-407(Cry(+)) strain, β-exotoxin I was produced from determinants located on a cry gene-bearing plasmid and that sigW is able to induce β-exotoxin I production in B. thuringiensis in the absence of cry gene-bearing plasmids. Although the signal responsible for this activation is unknown, these results indicate that β-exotoxin I production in B. thuringiensis can be restored or induced via an alternative pathway that requires sigW expression.